2017
DOI: 10.1186/s13578-017-0145-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of GLI1 for 5-Fu resistance in colorectal cancer

Abstract: Colorectal cancer is a leading cause of cancer-related mortality worldwide, with Fluorouracil (5-FU)-based chemotherapy as the major treatment for advanced disease. Many patients with advanced colorectal cancer eventually succumb to the disease despite some patients responded initially to chemotherapy. Thus, identifying molecular mechanisms responsible for chemotherapy resistance will help design novel strategies to treat colorectal cancer. In this study, we established an acquired 5-FU resistant cell line, Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…To understand the molecular basis underlying drug resistance of 5‐FU in colorectal cancer, we first generated 5‐FU resistant LoVo‐R cell line from the parental LoVo cells through gradual addition of 5‐FU for nearly a year . We compared gene expression between LoVo‐R and LoVo cells via RNA‐seq.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the molecular basis underlying drug resistance of 5‐FU in colorectal cancer, we first generated 5‐FU resistant LoVo‐R cell line from the parental LoVo cells through gradual addition of 5‐FU for nearly a year . We compared gene expression between LoVo‐R and LoVo cells via RNA‐seq.…”
Section: Resultsmentioning
confidence: 99%
“…Chemotherapeutic treatment of colorectal cancer is based on 5-fluorouracil (5-FU) which is an anticancer drug interfering with nucleoside metabolism through incorporation into RNA and DNA. This leads to cell death ( 6 , 19 , 20 ). After treatment of LoVo cells without altered expression of LMNB1 with 5-FU, we observed induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some pathways such as Hedgehog signaling, initially described as important regulators of embryonic development, tissue polarity, and cell differentiation (EMT), were also described to be involved in CRC development and 5‐FU resistance through an increase of GLI1 expression in 5‐FU‐resistant cells. Indeed, it was observed that GLI1 knockdown sensitized CRC cells to 5‐FU treatment, reducing tumor invasiveness 31 …”
Section: Cellular Functions Disrupted By 5‐fumentioning
confidence: 99%